2018
DOI: 10.3390/vetsci5010007
|View full text |Cite
|
Sign up to set email alerts
|

Owners and Veterinary Surgeons in the United Kingdom Disagree about What Should Happen during a Small Animal Vaccination Consultation

Abstract: Dog and cat vaccination consultations are a common part of small animal practice in the United Kingdom. Few data are available describing what happens during those consultations or what participants think about their content. The aim of this novel study was to investigate the attitudes of dog and cat owners and veterinary surgeons towards the content of small animal vaccination consultations. Telephone interviews with veterinary surgeons and pet owners captured rich qualitative data. Thematic analysis was perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
48
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(53 citation statements)
references
References 37 publications
5
48
0
Order By: Relevance
“…The majority of interviewees were female. This is compatible with other UK-based companion animal research involving owners [42] and is reflects a finding of greater levels of dog ownership amongst female study participants [52]. Additionally, women are more likely than men to take on caring roles in the household [53] and future research should investigate whether women also typically take on the role of pet carer in UK households.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The majority of interviewees were female. This is compatible with other UK-based companion animal research involving owners [42] and is reflects a finding of greater levels of dog ownership amongst female study participants [52]. Additionally, women are more likely than men to take on caring roles in the household [53] and future research should investigate whether women also typically take on the role of pet carer in UK households.…”
Section: Discussionsupporting
confidence: 82%
“…Traditionally, support for owners would be considered to be provided by the veterinary practice with the veterinary surgeon acting as diagnositician, key information source and gateway to accessing prescription medication. However, Christiansen and colleagues [25] identified that owners may not receive the support that they seek from their veterinary practice in relation to end of life decision making, and Belshaw and colleagues [42] identified mismatched expectations between veterinary surgeons and owners during preventive healthcare consultations. This is further illustrated by the anonymous owner of an osteoarthritic dog who wrote compellingly about her sense of isolation when she felt her local practice was not giving her the support she needed [43].…”
Section: Discussionmentioning
confidence: 99%
“…How best to apply epidemiology to promote disease detection and improve feline health remains a long‐standing topic of interest, especially because current metrics to assess disease have limitations. Age categories are considerably subjective, as designated, for example, by middle‐aged, adult, mature, senior, or geriatric labels that are commonly applied.…”
Section: Discussionmentioning
confidence: 99%
“…While interviewees were predominantly asked about the consultations rather than the preventative medicines, many of the interviewee responses focused on the discussion of preventative medicines themselves (Belshaw et al, 2018a). Where the consultation was discussed, experiences and expectations of the consultation appeared to vary widely, both between owners and veterinary surgeons, and between individuals within these subgroups (Belshaw et al, 2018b). There has been some controversy in recent years around pet vaccination, with some describing 'vaccinophobia' amongst pet owners (Day, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…However, previous research has suggested that preventative healthcare consultations differ considerably from health problem consultations in terms of communication style (Shaw et al, 2008) and content , and so appropriate measures of success may also be different for these consultations. In addition, recent research has found that owner and veterinary surgeon expectations of these consultations differs widely between individuals, and so different measures of success may be important to different people (Belshaw et al, 2018b).…”
Section: Introductionmentioning
confidence: 99%